Potential Role of Mesenchymal Stem Cells in Alleviating Intestinal Ischemia/Reperfusion Impairment - Jiang, Haitao (Public Library of Science, 2013)
BACKGROUND: Transplantation of bone marrow mesenchymal stem cells (MSCs) provides a promising therapeutic efficiency for a variety of disorders caused by ischemia or reperfusion impairment. We have previously demonstrated the efficacy of MSCs in mitigating intestinal ischemia/reperfusion (I/R) injuries in rats, but the mechanism by which MSCs engraft ameliorates I/R injuries has largely been unknown. The present study aimed at investigating probable mechanisms by which MSCs exert their function. METHODS: Male donor derived rat MSCs were implanted into intestine of female recipient rat by direct submucosal injection after superior mesenteric artery clamping and unclamping. The homed MSCs were detected by Y chromosome in situ hybridization probe, and the tumor necrosis factor-α (TNF-α) content in intestinal mucosa was determined by ELISA. Expression of proliferative cell nuclear antigen (PCNA) in bowel mucosa was assayed by real-time PCR and intestinal mucosa expression of phosphorylation extracellular signal-regulated kinase (pERK1/2) and nuclear factor-κB (NF-κB) were evaluated by western blot. RESULTS: Four and seven days after MSCs transplantation, the TNF-α content of bowel mucosa in MSCs group was significantly lower than that in saline group. The PCNA in bowel mucosa showed higher expression in MSCs treated group than the saline group, both at 4 and 7 days after cell transplantation. The expression of intestinal mucosal pERK1/2 in MSCs treated group was markedly higher than that in saline group, and the expression of NF-κB in MSCs treated group was noticeably decreased than that in saline group at 4 and 7 days post MSCs transplantation. CONCLUSION: The present investigation provides novel evidence that MSCs have the potential to reduce intestinal I/R injuries probably due to their ability to accelerate cell proliferation and decrease the inflammatory response within intestinal mucosa after ischemia and reperfusion.